Polymeric hydrogels as a vitreous replacement strategy in the eye. (January 2021) - Lin, Qianyu; Lim, Jason Y.C.; Xue, Kun; Su, Xinyi; Loh, Xian Jun
Abstract: Vitreous endo-tamponades are commonly used in the treatment of retinal detachments and tears. They function by providing a tamponading force to support the retina after retina surgery. Current clinical vitreous endo-tamponades include expansile gases (such as sulfur hexafluoride (SF6 ) and perfluoropropane (C3 F8 )) and also sislicone oil (SiO). They are effective in promoting recovery but are disadvantaged by their lower refractive indices and lower densities as compared to the native vitreous, resulting in immediate blurred vision after surgery and necessitating patients to assume prolonged face-down positioning respectively. While the gas implants diffuse out over time, the SiO implants are non-biodegradable and require surgical removal. Therefore, there is much demand to develop an ideal vitreous endo-tamponade that can combine therapeutic effectiveness with patient comfort. Polymeric hydrogels have since attracted much attention due to their favourable properties such as high water content, high clarity, suitable refractive indices, suitable density, tuneable rheological properties, injectability, and biocompatibility. Many design strategies have been employed to design polymeric hydrogel-based vitreous endo-tamponades and they can be classified into four main strategies. This review seeks to analyse these various strategies and evaluate their effectiveness and also propose the key criteria to design successful polymeric hydrogel vitreous endo-tamponades. Graphical abstract: Image 1